The innate immune response to products of phospholipid peroxidation() - Weismann, David (Elsevier Pub. Co, 2012)
Lipid peroxidation occurs in the context of many physiological processes but is greatly increased in various pathological situations. A consequence of phospholipid peroxidation is the generation of oxidation-specific epitopes, such as phosphocholine of oxidized phospholipids and malondialdehyde, which form neo-self determinants on dying cells and oxidized low-density lipoproteins. In this review we discuss evidence demonstrating that pattern recognition receptors of the innate immune system recognize oxidation-specific epitopes as endogenous damage-associated molecular patterns, allowing the host to identify dangerous biological waste. Oxidation-specific epitopes are important targets of both cellular and soluble pattern recognition receptors, including toll-like and scavenger receptors, C-reactive protein, complement factor H, and innate natural IgM antibodies. This recognition allows the innate immune system to mediate important physiological house keeping functions, for example by promoting the removal of dying cells and oxidized molecules. Once this system is malfunctional or overwhelmed the development of diseases, such as atherosclerosis and age-related macular degeneration is favored. Understanding the molecular components and mechanisms involved in this process, will help the identification of individuals with increased risk of developing chronic inflammation, and indicate novel points for therapeutic intervention. This article is part of a Special Issue entitled: Oxidized phospholipids—their properties and interactions with proteins.